Influence of enriched organic manure, biostimulants and bio-mulches on organic okra (Abelmoschus esculentus) - Mishra, Subha Laxmi; Chatterjee, Ranjit; Tamang, Amrit; Saha, Koushik (The Indian Journal of Agricultural Sciences, 2020)
Field experiments were conducted to identify the best source of nutrients and bio-mulch for fruit yield, quality and soil properties of organic okra (Abelmoschus esculentus) at U B K V, Pundibari, West Bengal, India during February- May 2017-18. The experiment was laid out in Factorial RBD comprising of two factors, viz. organic nutrient sources (N) and bio-mulches (M) having four levels each. The findings of the experiment suggested that basal application of Azophos biofertilizer enriched vermicompost (5 t/ha) along with foliar spray of seaweed extract (2 ml/l) at 30, 40 and 50 days of sowing (N4) emerged as best treatment in terms of highest number of fruits (19.94/plant) and maximum yield (14.39 t/ha). Among the different bio-mulches, the vegetable legume plant residue mulch (M4) recorded highest number of fruits (20.79/plant), total fruit yield (14.79 t/ha), maximum ascorbic acid content (18.47 mg/100 g) and increased total chlorophyll content (46.99 mg/100 g). The interaction of N4M4 recorded highest number of fruit (22.88/ plant), fruit yield (348.08 gm/plant), total yield (16.68 t/ha) and the maximum total fruit chlorophyll content (51.60 mg/100 g). All the interaction of organic nutrient sources and bio-mulches showed increase in available N, P, K and organic carbon content in post harvest soil over the initial status. The study concluded that adoption of biofertilizer enriched vermicompost in combination with 3 times foliar spray of seaweed extract in standing crop with legume as mulch have significant positive impact on fruit yield, quality and soil properties of organic okra.